2018
DOI: 10.1016/s0140-6736(18)30595-6
|View full text |Cite
|
Sign up to set email alerts
|

On the road to universal health care in Indonesia, 1990–2016: a systematic analysis for the Global Burden of Disease Study 2016

Abstract: SummaryBackgroundAs Indonesia moves to provide health coverage for all citizens, understanding patterns of morbidity and mortality is important to allocate resources and address inequality. The Global Burden of Disease 2016 study (GBD 2016) estimates sources of early death and disability, which can inform policies to improve health care.MethodsWe used GBD 2016 results for cause-specific deaths, years of life lost, years lived with disability, disability-adjusted life-years (DALYs), life expectancy at birth, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
148
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(174 citation statements)
references
References 23 publications
2
148
1
7
Order By: Relevance
“…Besides, our study represents more recent data (obtained in 2013) compared with the two previous studies which were conducted in 2000 and 2006, over which time the prevalence may have truly increased. Our results are in line with the growing national burden of non-communicable disease in Indonesia, as between 1990 and 2016 disability-adjusted life years (DALYs) had risen for non-communicable diseases, particularly ischemic heart disease, cerebrovascular disease, and diabetes as the three leading causes of DALYs [28]. This was also supported with previous studies that reported a rapid increase of the prevalence of overweight/obesity and diabetes in Indonesia over the past decades [29,30].…”
Section: Discussionsupporting
confidence: 91%
“…Besides, our study represents more recent data (obtained in 2013) compared with the two previous studies which were conducted in 2000 and 2006, over which time the prevalence may have truly increased. Our results are in line with the growing national burden of non-communicable disease in Indonesia, as between 1990 and 2016 disability-adjusted life years (DALYs) had risen for non-communicable diseases, particularly ischemic heart disease, cerebrovascular disease, and diabetes as the three leading causes of DALYs [28]. This was also supported with previous studies that reported a rapid increase of the prevalence of overweight/obesity and diabetes in Indonesia over the past decades [29,30].…”
Section: Discussionsupporting
confidence: 91%
“…In Indonesia, facility‐based childbirth is the norm for a large proportion of the population and will continue to expand given supportive government policies, including the national health insurance scheme initiated in 2014 . Ensuring that care provided in these facilities is of sufficient quality to support improvements in maternal and newborn outcomes and reductions in mortality is vital .…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] InIndonesia,facility-basedchildbirthisthenormforalargeproportion of the population and will continue to expand given supportive government policies, including the national health insurance schemeinitiatedin2014. 22 Ensuringthatcareprovidedinthesefacilitiesisofsufficientqualitytosupportimprovementsinmaternaland newborn outcomes and reductions in mortality is vital. 23 Improved provider practices to monitor the intrapartum period and prevent complications,aswellasfacilityreadinesstopreventand/ormanage adverse events, have been the focus of various quality assessment andimprovementefforts.…”
Section: Infection Prevention Practicesmentioning
confidence: 99%
“…If we look at the 10 most common diseases in the City of Parepare, some of them are preventable diseases, and diseases caused by unfavorable environmental conditions and the result of not implementing clean and healthy living behavior [23].…”
Section: Discussionmentioning
confidence: 99%